ASSESSMENT OF SEED EMERGENCE PERIODS AND INITIAL DEVELOPMENT OF GUAR — CYAMOPSIS TETRAGONOLOBA (L.) TAUB. UNDER RAINFED CONDITIONS OF GALLAOROL DISTRICT, JIZZAKH REGION (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
The article describes the introduction of guar — Cyamopsis tetragonoloba (L.) Taub. seed material into a field experiment, the sowing scheme, and emergence periods under the rainfed conditions of Gallaorol district, Jizzakh region. Guar seed material obtained from the Research Institute of Plant Genetic Resources was selected as the research object. The field experiment was established on 28 April 2026 on a total area of 120 m², in two replications, with a row spacing of 76 cm. Based on published data, the calculated 1000-seed weight was accepted as 32.8 g and the seeding rate as 15 kg ha⁻¹; accordingly, the calculated amount required for the experimental area was determined as 180 g, or approximately 5488 seeds. Initial seedlings were observed 3–5 days after sowing, while mass emergence was observed 12–14 days after sowing. The preliminary data obtained provide a methodological basis for assessing the initial development of guar under rainfed conditions through subsequent phenological and morphometric observations.
Keywords: Guar, Cyamopsis tetragonoloba, rainfed conditions, introduction, seed material, emergence, seeding rate, Jizzakh region.